Hyperbranched PDLA-polyglicerol: A novel additive for tuning PLLA electrospun fiber degradation and properties. (June 2017) - Gardella, Lorenza; Forouharshad, Mahdi; Pastorino, Laura; Monticelli, Orietta
Graphical abstract: Highlights: We develop the synthesis of a novel polymer additive. The additive is made up of a hyperbranched polyglicerol core and PDLA arms. The dendritic additive is found to enhance the fiber enzymatic degradation rate. The dendritic additive is found to increase the system mechanical properties. The increase of the mechanical properties is related to the stereocomplexation. Abstract: In this paper, it was developed the synthesis of a novel polymer additive potentially capable of modifying the features of electrospun fibers based on poly(l -lactide) (PLLA). Indeed, the above molecule, which was designed by taking into account both the features of the polymer matrix and the specific applications of the final material, was made up of a high-molecular-mass hyperbranched polyglicerol (HBPG) core and poly(d -lactide) (PDLA) arms (HBPG-PDLA). 1 H NMR characterization allowed to assess the successful preparation of the dendritic HBPG-PDLA, synthesized by means of ring opening polymerization (ROP) ofd -lactide, as well as the number average molecular weight per arm, that is about 1100 g/mol. Moreover, by combining 1 H NMR and TGA results, it was determined an average number of polylactide arms of about 300. Electrospun fibers based on PLLA and HBPG-PDLA were prepared by directly adding the as-synthesized dendritic additive into the electrospinning solution to a final concentration of ca. 25 wt.%. FE-SEM analysis of the system, prepared by applying the optimized electrospinning conditions, demonstrated the formation of defect-free fibers without separated, micrometric domains of the additive. The thermal properties of both neat PLLA and composite fibers were studied by DSC analysis. The partial stereocomplexation of the systems containing HBPG-PDLA, resulting from the combination of the PDLA arms of the dendritic polymer with the chains of PLLA, was confirmed by calorimetric measurements as well as by X-ray diffraction analysis. The dendritic additive, featuring the hyperbranched polyglycerol core, was found to enhance the hydrophilicity of the fibers and consequently their enzymatic degradation rate, which turned out to be much higher than that of the neat PLLA fibers. Unlike the organic additives usually applied to modify the properties of PLLA, the addition of HBPG-PDLA to the fibers was also found to lead to an increase of the mechanical properties of the composite systems, that is an increment of their Young's modulus.